"The more important findings are sustained": A diachronic perspective on the genre of the retraction notice. (July 2022) - Lin, Yuting; Chen, Meilin
Abstract: The retraction of flawed publications has been an integral part of the self-correcting mechanisms in modern science. This paper traces changes in the genre of the retraction notice (RN) by comparing its earlier (1966–1996) and current (2016–2020) forms. We used methods developed by Bhatia (2004) to analyze the rhetorical moves/steps and their linguistic realizations in 200 RNs from high-impact biomedical journals. Six of the eight moves we identified from the RNs are found to be more frequent in post-2016 RNs than in pre-1996 RNs. Specifically, the post-2016 RNs have two compulsory moves "Stating the error" and "Stating the author's decision", while the pre-1996 RNs do not. Further, more post-2016 RNs than pre-1996 RNs contain the moves "Noting the claimant", "Mitigating the error", "Showing corrective actions", and "Expressing the author's emotions". The results show that the genre of the RN is shaped by mixed influences from journals' standardization efforts as well as authors' own need for image repair. RNs should adhere more strictly to principles of evidence-based academic writing and disclose more fully the process of error correction to enhance the trustworthiness and usefulness of the genre. Highlights: We compare retraction notices (RNs) from the periods 1966–1996 and 2016–2020. The move structure of 200 RNs from high-impact biomedical journals were analyzed. Post-2016 RNs contain more compulsory moves, showing growing influence of policies. They also have more moves for image repair: mitigation, corrective action, apology. Baseless self-legitimation and incomplete error disclosure are persistent in RNs.